Hubungan Kesegaran Jasmani Dengan Kemampuan Shooting dalam Permainan Sepak Bola pada Pemain PS. Andeskal Muda Kota Bengkulu - Syaputra, Roni (UNIVED Press, Universitas Dehasen Bengkulu, 2020)
This study aims to determine the relationship of Physical Freshness and Shooting Ability in Football Games on PS Players. Andeskal Muda City of Bengkulu. This type of research is correlational with quantitative methods. The population in this study were PS players. Andeskal Muda Bengkulu City, amounting to 30 people. While the sampling technique was done by using the total sampling technique. Thus, the sample size is 30 people. Data was collected using the Indonesian Physical Fitness Test (TKJI) and the shooting ability test was carried out by the shooting at the ball test. The level of physical fitness of PS players. Andeskal city of Bengkulu had the lowest score of 11 categories with less and the highest score of 22 which was very good category, and the shooting ability had the lowest score of 24 poor categories and the highest score was 47 which was very good category. The results showed that the level of physical fitness of the players had a relationship with the results of the shooting ability of the PS players. Andeskal Muda city of Bengkulu, based on the value of rtable in the product moment obtained 0.361 then rejected Ho in the t analysis test obtained, tcount was 6.1978 greater than ttable is 2.048, the decision rejected the alternative hypothesis (Ho) and accepted the alternative hypothesis (Ha). So the conclusion is that there is a correlation between the TKJI test (variable x) and the shooting ability test (variable y) on PS players. Andeskal Muda city of Bengkulu, this is shown by the correlation coefficient of 0.76 which is in the strong category.